Analisis Hasil Penyelesaian Soal Integrasi Numerik Berbasis ChatGPT - Silvana Samaray (STIKes Ibnu Sina Ajibarang, 2024)
The use of artificial intelligence technology in education continues to evolve, one of which is through the application of ChatGPT. This study aims to analyze the results of solving numerical integration problems with the help of ChatGPT compared to manual methods. Numerical integration is an important method in mathematics and various disciplines for calculating the integral values of complex functions. However, manual methods require a deep understanding and high mathematical skills, with a considerable amount of time and repetitive processes that often result in inaccurate solutions. This research attempts to explore the potential of ChatGPT as an educational tool, which has not been extensively discussed in previous literature, especially in solving complex mathematical problems. In this study, a number of numerical integration problems were solved using manual methods, such as the Trapezoidl and Simpson's methods, as well as with the help of ChatGPT. The results were then compared in terms of solution accuracy. The research findings indicate that ChatGPT is capable of providing accurate solutions, with results comparable to manual methods in many cases. The analysis shows that ChatGPT can be used as an aid in solving numerical integration problems because it can provide accurate results comparable to manual methods. However, manual methods are still necessary to maintain a balance between understanding basic concepts and utilizing technology in learning.